Performance and stability of La0.8Sr0.2MnO3 cathode promoted with palladium based catalysts in solid oxide fuel cells - Babaei, A.; Zhang, L.; Liu, E.; Jiang, San Ping (Elsevier B.V., 2011)
The effect of catalyst loading, operation temperature and co-infiltration of the palladium-based catalystson the performance and stability of La0.8Sr0.2MnO3 (LSM) cathode of solid oxide fuel cells (SOFCs) isinvestigated. The result shows that adding a small amount of Pd catalyst (0.08mgcm-2) has a remarkable effect on the reduction of overpotential of LSM cathodes and high palladium loading is detrimental to the electrochemical activity of LSM cathodes. The performance and stability of the Pd-impregnated LSM cathodes can be enhanced significantly by co-infiltration of palladium with either 20 mol% of silver or 5 mol% of cobalt. Increased stability of the co-infiltrated catalyst materials is probably related to the enhanced resistance of the co-impregnated Pd0.95Co0.05 and Pd0.8Ag0.2 nanoparticles against agglomeration and sintering at SOFC operation temperatures. The results indicate the co-impregnation is effective not only to enhance the electrochemical activity but also to improve the stability of LSM cathodes for the O2 reduction reaction of SOFCs.